Investigation of surface roughness in micro-EDM of nonconductive ZrO2 ceramic with powder mixed dielectric fluid - Sabur, Abdus; Syed Mohammed, Mehdi; Ali, Mohammad Yeakub; Maleque, Md. Abdul; Moudood, M. A. (Trans Tech Publications, Switzerland, 2015)
This paper investigates the average surface roughness (Ra) in micro-electrical discharge machining of electrically nonconductive zirconium oxide (ZrO2) ceramic using powder mixed dielectric. The gap voltage and concentration of tantalum carbide (TaC) powder are considered as the variable parameters for the investigation while other conditions are kept constant. Response surface methodology is used for design of experiments and to analyze the results for a better surface finish. The study shows that both the gap voltage and powder concentration have a significant effect on the average surface roughness of ZrO2. However, voltage has the higher effect than powder concentration on the surface integrity. The optimized values of gap voltage and powder concentration are found to be 94.39 V and 6.28g/l respectively for a minimum surface roughness in micro-EDM of ZrO2.